1986
DOI: 10.1029/gl013i012p01248
|View full text |Cite
|
Sign up to set email alerts
|

Total ozone decrease at South Pole, Antarctica, 1964‐1985

Abstract: Mean monthly total ozone data obtained at South Pole, Antarctica, during 1964‐1985 are presented. Preliminary analysis of the data suggests that total ozone has decreased at South Pole by roughly 20% since the mid‐1960's. Largest decreases have occurred during October and November months, but autumn and winter months also exhibit a decrease. During February months, ozone has increased slightly. Superimposed on the long‐term downward ozone trend are episodic decreases in ozone dating back to 1965 that have occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
14
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 3 publications
2
14
0
Order By: Relevance
“…GARDINER and SHANKLIN (1986) showed that the decrease continued up to 1985. Similar changes were reported for Syowa (69~ 39~ and at the South Pole (CHUBACHI and KAJIWARA, 1986;KOMHYR et ,al., 1986;BOJKOV, 1986a,b). For the Argentine Islands (65~ 64~ FARMAN et al (1985) reported changes similar to those at Halley Bay but much smaller in magnitude.…”
Section: Introductionsupporting
confidence: 88%
“…GARDINER and SHANKLIN (1986) showed that the decrease continued up to 1985. Similar changes were reported for Syowa (69~ 39~ and at the South Pole (CHUBACHI and KAJIWARA, 1986;KOMHYR et ,al., 1986;BOJKOV, 1986a,b). For the Argentine Islands (65~ 64~ FARMAN et al (1985) reported changes similar to those at Halley Bay but much smaller in magnitude.…”
Section: Introductionsupporting
confidence: 88%
“…The relative contributions to polar vortex stability by ozone-related heating and ENSO-and QBO-induced changes in atmospheric circulation are difficult to assess. It is worth noting, however, that large differences in the time of springtime stratospheric warming in Antarctica are evident in records dating back to the early 1960s [Komhyr et al, 1986], a time when destruction of ozone by chlorine trace gas species was presumably negligible.…”
mentioning
confidence: 86%
“…Recent measurements have characterized the environment of the polar stratosphere, which correlates to the large depletion of ozone in the austral spring. The specific conditions they found are: low temperatures which produce polar stratospheric clouds (PSC's), large concentrations of chlorine oxides, and the appearance of sunlight needed to drive photochemical reactions [l, 21. Field observations found that the ozone decrease displayed a temporal correlation with increasing concentration of atmospheric chlorine [3,4]. In this paper we reexamine the gas phase and heterogeneous photoreactivity of chlorine dioxide, OC10.…”
Section: Introductionmentioning
confidence: 99%